2001
DOI: 10.1021/ie0011167
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Zn−Ti-Based H2S Removal Sorbents Promoted with Cobalt Oxides

Abstract: Modification of conventional zinc titanate (ZT) sorbents to increase their reactivity and stability during multiple cycles of sulfidation/regeneration at high and middle temperatures was pursued by addition of Co 3 O 4 . Moreover, evaluation of the modified zinc titanates (ZTC) was conducted using several instruments such as an X-ray diffractometer, Fourier transform infrared spectrometer, scanning electron microscope, and so on. The ZTC sorbents prepared by the physical mixing of the ZT sorbent with 25 wt % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 24 publications
6
57
0
Order By: Relevance
“…The sample Co 7 Sb 2 O 12 ( Figure 11) presented four bands that can be attributed to the spinel structure. These were in the regions: 19 and Jun et al 20 observed that Co 3 O 4 absorbs in the regions near 210, 216, 560 and 660 cm -1 . Thus, the additional bands can be related to the presence of Co 3 O 4 , which was not observed by X-ray diffraction.…”
Section: Resultsmentioning
confidence: 84%
“…The sample Co 7 Sb 2 O 12 ( Figure 11) presented four bands that can be attributed to the spinel structure. These were in the regions: 19 and Jun et al 20 observed that Co 3 O 4 absorbs in the regions near 210, 216, 560 and 660 cm -1 . Thus, the additional bands can be related to the presence of Co 3 O 4 , which was not observed by X-ray diffraction.…”
Section: Resultsmentioning
confidence: 84%
“…This is due to its direct relationship with anisotropy constant of the sample. The anisotropy constant decreases with increasing Zn 2+ content, which in turn decreases the domain wall energy [25,26].…”
Section: +mentioning
confidence: 99%
“…Hence in the multi domain region the coercivity decreases as the particle diameter increases. A decrease in coercivity as observe in Figure 6, with increase in zinc concentration may be attributed to the decrease in anisotropy field, which in turn decreases the domain wall energy [18,19]. …”
Section: Magnetic Measurementsmentioning
confidence: 99%